Web Application Models Are More Than Conceptual Models - Rossi, Gustavo Héctor (1999)
In this paper we argue that Web applications are a particular kind of hypermedia application and show how to model their navigational structure. We argue that if we need to design applications combining hypermedia navigation with complex transactional behaviors (as in E-commerce systems), we need a systematic development approach. We present the main ideas underlying the Object-Oriented Hypermedia Design Method (OOHDM) and show that Web applications are built as views of conceptual models. We present the abstraction primitives used to design conceptual and navigational structure of Web applications and describe the view definition language. We introduce navigational contexts as the structuring mechanism for the navigational space. Further work on designing Web applications with OOHDM is also presented.